Orang Asli in Politics in Development of Pahang - Othman, Omar (2004)
The research is carried out to determine the role and involvement of the Orang Asli community in the politics and development in Pahang. The study aims to gauge their views and knowledge in the two fields. The study engages several concepts in the fields of politics and development. This study will also review previous researches and studies in the same field. Various research methods are used such as survey, informal interview, literature research and personal experiences. Analysis begins by looking at the political structure of the Orang Asli community, their involvement in politics as well as their views and knowledge of development. In addition, the study also examines the role of the government in aiding the development of the Orang Asli community in Pahang. Study findings reveal that on the whole, the Orang Asli’s involvement in politics is satisfactory. Their involvement in the electoral process—i.e. voting—are quite high. On political knowledge, the study found that the Orang Asli’s knowledge in this areas is high. This is concluded from the fact that the Orang Asli are very familiar with their local assemblyman. However, it is noted that the level of participation and understanding varies from group to group and from area to area. In the aspect of development, research findings show that a majority of the Orang Asli community have actually participated directly in development and that some have also benefited from it especially in the form of infrastructure development. With respect to their knowledge of development, a larger proportion of the Orang Asli knew what the term “development” generally entails. However, the study found that although involvement and knowledge is high, this various between areas and is not uniform throughout the Orang Asli settlement. Therefore, relevant authorities, involved in the development of the Orang Asli community should take drastic measures to ensure the participation of these citizens be more comprehensive in politics and development in Pahang.